Immunochemical markers of effect under exposure to risk factors causing vibration disease of different etiogenesis: сomparative assessment - G.M. Bodienkova; E.V. Boklazhenko (Analiz Riska Zdorovʹû, 2023)
In recent years, it has become especially vital to identify prognostic risks of health disorders in workers exposed to harmful occupational factors. This is necessary for substantiating an occupational origin of a disease and biomarkers of exposure and for optimizing the occupational risk assessment methodology.